2020
DOI: 10.1007/s13205-020-02459-z
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis TR47II as a source of bioactive lipopeptides against Gram-negative pathogens causing nosocomial infections

Abstract: This study aimed to investigate the antimicrobial, antibiofilm, and cytotoxic effects of biosurfactant lipopeptides synthesized by Bacillus subtilis TR47II. For this purpose, the lipopeptides were partially purified using a three-step process and characterized. In the first step, the crude extract obtained from acid precipitation exhibited strong antibacterial activity against the Gram-negative opportunistic pathogens Alcaligenes faecalis ATCC 8750, Achromobacter xylosoxidans ATCC 13138, Pseudomonas alcaligene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Cyclic lipopeptides have a wide range of biological activities, including antimicrobial, antiviral, anticancer and immunosuppressive activities, and have specific mechanisms that affect membrane permeability, eventually leading to cell disuption [41]. The same conclusion was obtained among studies of Fernanda (2020), their result showed the lipopeptides'capability to disturb the structure and functions of biological membranes, leading to the increased membrane permeability [42]. Ongena and Jacques [43] used a versatile weapons for plant disease biocontrol to describe Bacillus lipopeptides and the recent investigations have shed light on the fact that lipopeptides play a key role in the beneficial interaction of Bacillus species with parasitic plants by stimulating its host defence mechanisms.…”
Section: Discussionmentioning
confidence: 58%
“…Cyclic lipopeptides have a wide range of biological activities, including antimicrobial, antiviral, anticancer and immunosuppressive activities, and have specific mechanisms that affect membrane permeability, eventually leading to cell disuption [41]. The same conclusion was obtained among studies of Fernanda (2020), their result showed the lipopeptides'capability to disturb the structure and functions of biological membranes, leading to the increased membrane permeability [42]. Ongena and Jacques [43] used a versatile weapons for plant disease biocontrol to describe Bacillus lipopeptides and the recent investigations have shed light on the fact that lipopeptides play a key role in the beneficial interaction of Bacillus species with parasitic plants by stimulating its host defence mechanisms.…”
Section: Discussionmentioning
confidence: 58%
“…It has been well characterized that Bacillus strains are able to synthesize various secondary metabolites, including fengycin, iturin, surfactin, difficidin, bacilysin, bacillibactin, bacillaene, amylocyclicin, subtilosin A, sublancin, and macrolactin, that possess antibacterial activity (Wilson et al, 1987;Scholz et al, 2014;Cavera et al, 2015;Liu et al, 2019;de Souza Freitas et al, 2020;Lv et al, 2020;Li et al, 2021a;Chakraborty et al, 2022;Erega et al, 2022;Zhou et al, 2022). There is a recent study showing that the transportation of bacilysin and bacillaene can be affected by RND-type transporters in Campylobacter jejuni (Erega et al, 2022).…”
Section: Investigation Of the Tolc Effect On The Susceptibility Of Eb...mentioning
confidence: 99%
“…Hassallidins are so far the only known cyanobacterial antifungal cyclic lipopeptides with an exocyclic peptide moiety (Neuhof et al, 2005; Neuhof, Schmieder, et al, 2006). In this sense, they are analogous to the bacterial lipopeptide fengycin, which is shown to act on both bacteria and fungi but does not affect mammalian cells (de Souza Freitas et al, 2020; Desmyttere et al, 2019; Lin et al, 2020). Hassallidins were reported to possess promising antifungal activities with low minimum inhibitory concentration values ranging from 0.29 to 8.0 μM against Candida strains (Neuhof et al, 2005; Neuhof, Schmieder, et al, 2006; Neuhof, Seibold, et al, 2006; Shishido, Humisto, et al, 2015; Shishido, Jokela, et al, 2015).…”
Section: Hassallidins and Balticidinsmentioning
confidence: 99%